Novel Immunochromatographic Test for Anti-factor XIII B Subunit Autoantibodies to Diagnose Autoimmune Acquired Factor XIII Deficiency - Osaki, Tsukasa; Yokoyama, Chikako; Magari, Yasuo; Souri, Masayoshi; Ichinose, Akitada (Thrombosis and Haemostasis, 2023)
Autoimmune factor XIII (FXIII) deficiency (AiF13D) is an acquired life-threatening bleeding disorder due to anti-FXIII autoantibodies (autoAbs). We previously established an immunochromatographic test (ICT) for detection of anti-FXIII-A subunit (FXIII-A) autoAbs. Conversely, the detection of anti-FXIII-B subunit (FXIII-B) autoAbs is currently performed in a limited number of medical facilities through time-consuming and expensive laboratory tests, such as dot-blotting analysis and enzyme-linked immunosorbent assay (ELISA). Accordingly, in this study, we generated eight rat monoclonal antibodies (mAbs) against human FXIII-B using the rat lymph node method. By employing an ELISA, two mAbs, 2G12B10 and 8H12B9, were selected considering the distance between the recognition regions of each mAb (the 6th and 9th–10th Sushi domain, respectively) and the strength of their reactivity. Using this mAb combination, we prototyped an ICT to detect anti-FXIII-B autoAbs and distinguish between AiF13D and “nonimmune” acquired FXIII deficiency (acF13D), and tested it with 22 healthy controls, 23 acF13D patients, 15 AiF13D patients without anti-FXIII-B autoAbs, and 8 AiF13D patients with anti-FXIII-B autoAbs. Receiver operating characteristic curve analyses of ICTs for anti-FXIII-B autoAbs were performed and revealed a precision similar to dot-blot analysis. Human anti-FXIII-A mAbs were also generated from a single patient with AiF13D using a new cDNA cloning method, and their binding properties were characterized. Consequently, anti-FXIII-A immunoglobulin G preparations were established as potentially permanent positive controls of ICT for anti-FXIII-A antibodies. Combining the previously developed ICT for anti-FXIII-A autoAbs and the novel ICT for anti-FXIII-B autoAbs may reduce false negatives and lead to appropriate diagnosis and treatment.
Keywords: bleeding disorder; autoimmune coagulation factor deficiencies; autoantibody; immunochromatography; point-of-care-tests